2022
DOI: 10.1093/iob/obac027
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the Bonnethead Shark (Sphyrna tiburo) Olfactory Rosette

Abstract: The unusual shape of sphyrnids (hammerhead sharks) heads has led to many functional hypotheses of potential sensory advantages and enhanced olfactory performance. Recent investigations into the flow of water within the sphyrnid olfactory chamber demonstrate that this complex structure exhibits a differential pressure system between the two nares that induces flow through the chamber. This leads to differential fluid velocities in different parts of the olfactory chamber. Particularly, lamellae at the medial en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similarly, previous work in salmonids showed that the convex areas of the secondary folds lack ORNs (Kudo et al, 2009 ; Olsen, 1993 ; Yamamoto & Ueda, 1977 ). This is in contrast to many elasmobranch fishes, where the sensory epithelium covers the secondary lamellae (both troughs and peaks), with areas of nonsensory epithelium along the inner margins of the lamellae and/or as intermittent projections into the sensory regions in some species (e.g., Camilieri‐Asch, Shaw, et al, 2020 ; Schluessel et al, 2008 ; Theiss et al, 2009 ; Simonitis & Marshall, 2022 ). In adult sockeye salmon, as in other salmonids, the sensory epithelium lies only along the troughs of the secondary folds, while the nonsensory epithelium covers the secondary lamellar peaks (Figure 5c ).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, previous work in salmonids showed that the convex areas of the secondary folds lack ORNs (Kudo et al, 2009 ; Olsen, 1993 ; Yamamoto & Ueda, 1977 ). This is in contrast to many elasmobranch fishes, where the sensory epithelium covers the secondary lamellae (both troughs and peaks), with areas of nonsensory epithelium along the inner margins of the lamellae and/or as intermittent projections into the sensory regions in some species (e.g., Camilieri‐Asch, Shaw, et al, 2020 ; Schluessel et al, 2008 ; Theiss et al, 2009 ; Simonitis & Marshall, 2022 ). In adult sockeye salmon, as in other salmonids, the sensory epithelium lies only along the troughs of the secondary folds, while the nonsensory epithelium covers the secondary lamellar peaks (Figure 5c ).…”
Section: Discussionmentioning
confidence: 89%